THE ARTISTIC REPRESENTATION OF CHARACTERS IN THE NOVEL “PRIDE AND PREJUDICE” BY JANE AUSTEN (Ideal Journal of Multidisciplinary Research, 2026)
The article examines the artistic representation of characters in the novel Pride and Prejudice by Jane Austen. The research focuses on the author’s methods of characterization and the ways in which social, moral, and psychological features of the characters are revealed through narrative techniques, dialogue, and situational conflicts. The study analyzes the central figures of the novel, particularly Elizabeth Bennet and Mr. Darcy, as well as several secondary characters who contribute to the development of the thematic structure of the work. Using literary-analytical and comparative methods, the article demonstrates that Austen’s artistic mastery lies in her ability to combine irony, social observation, and psychological depth in the depiction of characters. The results show that characterization in the novel not only reflects the social realities of early nineteenth-century England but also conveys universal moral values such as personal integrity, self-reflection, and emotional maturity.
Keywords: Characterization, artistic representation, narrative technique, social values, moral development, English literature, novel analysis.